التمثيل السياسي كنمط للحكم .... - حلواجي, عبد الفتاح (جامعة الوادي University of Eloued, 2018)
يشير مفهوم التمثيل السياسي في مختلف اللغات إلى الشَبَهِ أو المماثلة والتماثل في أكثر الصفات بين الأصل والممثل عنه أو المنوب، واصطلاحا إلى أنه عبارة عن إجراءات ومراحل تصل في الأخير إلى عملية تفويض تهدف إلى التعبير عن أولويات الناخبين عبر آلية الإنتخاب. ويفسر التمثيل السياسي بشقين، اجتماعيا بأنه ذو طابع رمزي يكون فيه المنتخبون صورة عن المجتمع الذي يمثلونه، وقانونيا تدور حول مفهوم التعاقد، وقد تنوعت رؤى المفكرين السياسيين الغربيين حول التمثيل السياسي، إذ دافع جون استيوارت ميل عن الفكرة بالشكل الذي يؤدي إلى قيم الحرية الفردية، أما مونتيسكيو فله إضافات عملية للتمثيل السياسي في الجوانب المتعلقة بمصدر اختيار الهيئة التمثيلية أي السلطة التشريعية، أما ماكس فيبر فيرى أن مصدر الشرعية التي يكتسبها الحكام هي وجه آخر للتمثيل السياسي، غير أن جون جاك روسو يرفض فكرة التمثيل السياسي في سياق دفاعه عن شكل الديمقراطية المباشرة معتبرا أنّ التمثيل انتقاص لها. Abstract: The concept of political representation in different languages indicates similarities, identification and symmetry between the original and the representative or the surrogate, and is idiomatically procedures and stages which ultimately reach a process of delegation aimed to express the priorities of the voters through the electoral mechanism. Political representation in two parts is interpreted, socially symbolic where the elected image of the society in which they represent, and legally revolves around the concept of contracting. The contributions of Western political thinkers have varied on political representation; John Jacques Rousseau is based on his refusal to act in the context of his defense of the form of direct democracy, John Stewart Mill defended the idea in a way that leads to the values of individual freedom, Montesquieu has practical additions to political representation in the aspects of the source of the selection of the representative body i.e. the legislative authority and Max Weber believes that the source of legitimacy Which the leaders acquire is another facet of political representation .
مناقشة للمضمون الإجتماعي، التصورات الفكرية والنظريات التفسيرية
Keywords: التمثيل السياسي؛ العملية القيادية؛ الوكالة؛ فكرة النموذج